Analisis Sistem Perencanaan dan Penganggaran Pendidikan Berbasis RKAM dalam Perspektif Efektivitas Pembiayaan: Studi Kasus di MA Al-Marfuiyah Cibadak Sukabumi - Nadia Rahayu; Nada Shofa Lubis (Perkumpulan Peneliti dan Pegiat Literasi, 2026)
This study analyzes the planning and budgeting system based on RKAM from the perspective of financing effectiveness at MA Al-Marfuiyah Cibadak Sukabumi. The problem addressed in this study is that RKAM is often treated as an administrative budgeting document rather than an instrument for controlling educational financing effectiveness. This study used a qualitative case study design. Data were collected through interviews, document analysis, and limited observation when needed. The data were analyzed by identifying the relationship between educational needs, program priorities, funding sources, budget allocation, implementation evidence, and educational outputs. The findings show that RKAM at MA Al-Marfuiyah has functioned as a formal and structured planning document. It links vision, mission, programs, funding sources, schedules, and the eight National Education Standards. However, its effectiveness is still stronger at the administrative and operational levels than at the substantive outcome level. Several programs have budget allocations, but not all are supported by measurable output and outcome indicators. This study contributes to educational financing literature by positioning RKAM as an effectiveness-oriented management instrument, not merely a compliance document.